Strategi pengembangan wisata budaya lokal berkelanjutan di Desa Sendang Duwur - Vidia Ali Syaharani; Arief Sudrajat (Departemen Pendidikan Sosiologi FISHIPOL UNY, 2024)
Village tourism can offer a unique experience while maintaining local culture and environmental aspects. East Java has the potential for village tourism, and Sendang Duwur Tourism Village is one example of sustainable implementation. The village offers cultural traditions, rituals, religious tourism, and creative economic activities. The focus of this research is on the dynamics of local culture and tourism development in Sendang Duwur Tourism Village. Modernization theory was used to analyze how tourism can bring changes to the values, traditions, behaviors, and lifestyles of the people in Sendang Duwur Village. Qualitative descriptive methodology was used, involving 5 resource persons and in-depth interview techniques, observation, and documentation. As a result, the development strategies include improving infrastructure, human resources, and promotion. The government also has a role in supporting the development of tourist villages, in addition to strategies that can be applied in the theory of sustainable modernization is that it must focus on the conservation of local culture, diversification of tourism products, and the use of technology.